2019
DOI: 10.1063/1.5094100
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electron surface interactions in geometrically symmetric capacitive RF plasmas in the presence of different electrode surface materials

Abstract: Particle-in-cell/Monte Carlo collision (PIC/MCC) simulations are performed to investigate the asymmetric secondary electron emission (SEE) effects when electrons strike two different material electrodes in low pressure capacitively coupled plasmas (CCPs). To describe the electron-surface interactions, a realistic model, considering the primary electron impact energy and angle, as well as the corresponding surface property-dependent secondary electron yields, is employed in PIC/MCC simulations. In this model, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Plasma generated at atmospheric pressure is also important. It can have a high density and a small spatial range, making it useful for the precise surface treatment of materials [4][5][6]. For example, such plasmas can reduce costs and improve efficiency in chip manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma generated at atmospheric pressure is also important. It can have a high density and a small spatial range, making it useful for the precise surface treatment of materials [4][5][6]. For example, such plasmas can reduce costs and improve efficiency in chip manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The realistic implementation of plasma-surface interactions include energy and material dependent ion induced secondary electron emission (γ-electrons), electron induced secondary electron emission (δ-electrons), elastic electron reflection as well as inelastic backscattering of electrons. Previous studies demonstrated the importance of including such processes realistically [59][60][61][62][63][64][65][66] and also showed that using two different boundary surface materials at both electrodes can induce a plasma asymmetry [67][68][69][70]. Such surface material asymmetries often occur in actual plasma processes and are also studied in this work.…”
Section: Introductionmentioning
confidence: 70%
“…The ion-induced SEE is usually counted if the electron temperature is low and the wall material is metallic, which has a lower electron-induced SEE coefficient. Taking the example of plasma processing using capacitively coupled plasma, it is usually the ion-induced SEE that is counted since electrodes are typically metallic and the electron temperature is low [44], whereas the electron-induced SEE was shown to be influential if the neutral pressure is low and the electrodes are made of a more emissive material such as SiO 2 [45].…”
Section: Electron Sheath Modeling Considering the Plasma-surface Inte...mentioning
confidence: 99%